2018
DOI: 10.1007/s12079-018-0470-6
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant Wnt Signaling Pathway in the Hematopoietic Stem/Progenitor Compartment in Experimental Leukemic Animal

Abstract: The evolutionarily conserved Wnt signaling pathway regulates physiological hematopoiesis, a process of formation of blood cells and has been shown to play crucial role in the development of both myeloid and lymphoid malignancies. The Wnt signaling pathway can be broadly divided into canonical and non-canonical pathways. In the present study, we investigated the pathobiology of leukemia by studying the expression profile of Wnt proteins, receptors, key signaling intermediates and endogenous Wnt antagonist invol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 61 publications
0
13
0
Order By: Relevance
“…Molecules involved in the modulation of hematopoiesis have been known for decades, but the introduction of Wnt signaling in this context changed how we understand this system, from early development to aging and disorders [ 109 ]. Wnt signaling and its crosstalk with well-known cytokines and other mediators further elucidate events such as HSC quiescence, proliferation, differentiation, and cell death.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Molecules involved in the modulation of hematopoiesis have been known for decades, but the introduction of Wnt signaling in this context changed how we understand this system, from early development to aging and disorders [ 109 ]. Wnt signaling and its crosstalk with well-known cytokines and other mediators further elucidate events such as HSC quiescence, proliferation, differentiation, and cell death.…”
Section: Discussionmentioning
confidence: 99%
“…In CML, whilst in vivo leukemic stem cells’ (LSC) survival was not affected by the inhibition of β-catenin signaling, it was in vitro [ 105 ], suggesting the involvement of other factors in a complex mechanism [ 107 ]. As a matter of fact, for CML, there is evidence that Wnt5a have β-catenin-dependent effects [ 105 ], whereas, in vivo, Wnt5a and DKK1 were described to act as proinflammatory agents and contribute to tumor suppression [ 78 , 108 , 109 ], hampering the understanding of Wnt5a in this context.…”
Section: Hematopoietic Malignancesmentioning
confidence: 99%
“…Nevertheless, these observations should be interpreted cautiously as these inhibitors might be β‐catenin unspecific, thus affecting other pharmacological targets. Besides, profound upregulation of the canonical Wnt3a/β‐catenin/CyclinD1 signaling axis has been observed in the leukemic HSPC compartment of NEU‐induced experimental leukemia, while the non‐canonical Wnt signaling with tumor‐supressing effects in hematologic malignancies, is suppressed . Given the essentiality of β‐catenin in hematological malignancies and LICs maintenance, its targeting, or its cooperative partners targeting, could open up new therapeutic strategies …”
Section: β‐Catenin Is Involved In T‐cell Leukemia Processes In Differmentioning
confidence: 99%
“…[27][28][29][30] Numerous studies have found Wnt signaling deregulation in many hematologic diseases such as leukemia and myelodysplastic syndrome. [31,32] Broadly, Wnt signaling is divided into two branchescanonical, which require β-catenin, and noncanonical, which apparently do not require β-catenin for signal transduction. The activation of canonical Wnt signaling involves binding of Wnt protein to the seven-pass transmembrane receptor Frizzledleading to the accumulation of β-catenin in the cytoplasm followed by its nuclear localization.…”
Section: Introductionmentioning
confidence: 99%
“…In the nucleus, β-catenin interacts with T-cell factor/lymphoid enhancer factor complex and activates downstream target genes to exert its biological activities. [32][33][34] Apart from signaling pathways, existence of a healthy hematopoietic microenvironment is also crucial to sustain normal hematopoietic activity. Bone marrow microenvironment (BME) is a cellular sanctuary composed of a variety of mesenchymal stromal cells, such as osteoblasts, endothelial cells, macrophages, reticular cells, adipocytes, and so forth.…”
Section: Introductionmentioning
confidence: 99%